Identification of Suicidal Ideation and Support for Families in Sub-Saharan Africa - Reuben Mwangi; Ellen Armbruster (Pan-African Journal of Health and Environmental Science)
Over 77% of global suicides related to life stress in 2019 occurred in low-income and middle-income countries. However, few studies in sub-Saharan Africa have focused on mental health and suicidal behaviors. Less than 10% of African countries have reported suicide rates (WHO, 2021). This article intends to raise awareness of the current global problem of suicide, especially in Africa, and its impact on families in Africa. This includes the pervasive nature of suicidal behavior and how it has been addressed in various parts of Africa. This research established that multiple studies from outside Africa, including high-income countries, address suicide symptoms and treatment. However, discussing this topic within an African cultural context is necessary. Psychoeducation and innovations such as telepsychiatry increase public awareness and access to services, and are essential aspects of addressing the problem of suicide in Africa. Family support, suicide prevention strategies, and psychotherapeutic interventions may also provide critical assistance before and during crises. This research highlights a traditionally taboo subject in sub-Saharan Africa, attempts to destigmatize it, and includes care, recommendations, and family coping skills.